Building a personal mobility device - Mohamed Nur Hidayat Mohamed Monjiat (2019)
Personal Mobility Devices (PMD) are lightweight electric vehicles that provides an alternative mobility option to automotive. Examples of PMDs include electric scooters, Segways, Hoverboards and many more. In recent years, PMDs have seen an increase in popularity worldwide as indicated in the 2016 Transparency Market Research [5], and this popularity is evident in Singapore as well. However, as PMD brings about additional benefits in terms of mobility, it poses potential dangers and risks as well to pedestrians, as argued by Litman and Blair [6]. Thus, the Land Transport Authority (LTA) devised various rules and regulations to be imposed on PMDs before they are allowed to be used on public paths [7]. This project is a continuation of previous students prototype and improvements are made to the electric scooter after a prototype analysis. This project focuses on adding a platform to the bare frame of the electric scooter prototype as well as a removable folding seat which allows the user to use the electric scooter whist seated or standing. Modelling of the platform and seat were done in Solidworks 2018. After the design stage, each components were built, assembled, and implemented onto the electric scooter prototype.